The Selective Autophagy Receptor Optineurin in Crohn’s Disease - Tschurtschenthaler, Markus; Adolph, Timon Erik (Frontiers in Immunology, 2018)
Autophagy is a pathway that allows cells to target organelles, protein complexes or invading microorganisms for lysosomal degradation. The specificity of autophagic processes is becoming increasingly recognised and is conferred by selective autophagy receptors such as Optineurin (OPTN). As an autophagy receptor, OPTN controls the clearance of Salmonella infection and mediates mitochondrial turn-over. Recent studies demonstrated that OPTN is critically required for pathogen clearance and an appropriate cytokine response in macrophages. Moreover, OPTN emerges as a critical regulator of inflammation emanating from epithelial cells in the intestine. OPTN directly interacts with and promotes the removal of inositol-requiring enzyme 1α (IRE1α), a central inflammatory signalling hub of the stressed endoplasmic reticulum (ER). Perturbations of ER and autophagy functions have been linked to inflammatory bowel disease and specifically Crohn’s disease. Collectively, these studies may explain how perturbations at the ER can be resolved by selective autophagy to restrain inflammatory processes in the intestine and turn the spotlight on OPTN as a key autophagy receptor. This review covers a timely perspective on the regulation and function of OPTN in health and inflammatory bowel disease.